Ovarian Cancer Metastasis to the Breast: A Case Report and Review of the Literature - Caruso, Giuseppe (Case Rep Oncol, 2020)
Although ovarian cancer often presents as a widespread disease, metastases to the breast and/or axillary lymph nodes are a very rare event, accounting for only 0.03–0.6% of all breast cancers. Its early recognition and accurate distinction from primary breast cancer are of crucial importance to choose an adequate systemic therapy over unnecessary surgeries. We presented the case of a 53-year-old woman who was diagnosed with breast metastases 2 years after the diagnosis of advanced primary serous ovarian cancer. The patient underwent primary cytoreductive surgery and platinum-based chemotherapy in combination with bevacizumab, followed by bevacizumab maintenance for 18 months. After 2 years of negative follow-ups, the disease unexpectedly spread to the left breast and axillary lymph nodes. No axillary lymph node dissection or breast surgery was performed. The patient received axillary radiotherapy and multiple chemotherapy lines: gemcitabine/cisplatin, liposomal doxorubicin, topotecan, olaparib/cediranib, paclitaxel, and cisplatin. Unfortunately, none of these treatments improved her prognosis and she died 3 years after the disease recurrence. Ovarian cancer metastasis to the breast reveals a disseminated disease with a poor prognosis. Currently, no valid treatment options are available as the disease shows multidrug chemoresistance. In the era of precision medicine, the characterization of genetic and molecular markers may play a role in offering new promising targeted therapies.